2012
DOI: 10.5692/clinicalneurol.52.416
|View full text |Cite
|
Sign up to set email alerts
|

Potent primary leptomeningeal lymphoma masquerading tuberculous meningitis -A case report

Abstract: A 45-year-old man presented with fever, progressive mutism and memory loss, was admitted to our hospital. MR imaging and angiography suggested multiple foci of infarctions and vasculitis without Gadrinium-enhancement. CSF examination revealed pleocytosis with mononuclear cell dominance and elevated protein content. Adenosine deaminase activity was accelerated, and no malignant cell was found. Whole body CT imaging and Garium-scintigraphy were normal. Under the clinical diagnosis of tuberculous meningitis, anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In addition to its significant value for the diagnosis of TBM, elevated CSF ADA levels can suggest other diseases, such as nontuberculous infectious meningitis ( 7 - 13 ), lymphoproliferative disorders ( 14 , 15 ), and autoimmune-related CNS disease ( 16 - 20 ). In particular, a recent retrospective study found that the elevation of ADA levels was a unique CSF finding in patients with autoimmune GFAP astrocytopathy ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its significant value for the diagnosis of TBM, elevated CSF ADA levels can suggest other diseases, such as nontuberculous infectious meningitis ( 7 - 13 ), lymphoproliferative disorders ( 14 , 15 ), and autoimmune-related CNS disease ( 16 - 20 ). In particular, a recent retrospective study found that the elevation of ADA levels was a unique CSF finding in patients with autoimmune GFAP astrocytopathy ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying the CSF ADA elevation in our patients remains unclear. High CSF ADA levels have also been reported in cases of Listeria meningitis (5), pneumococcal meningitis (6), and Cryptococcal meningitis (7), as well as leptomeningeal gliomatosis (8) and CNS lymphoma (9). A major function of ADA is related to lymphocyte proliferation and differentiation; ADA activity is found to be elevated with the cell-mediated immune response and is a marker of cellular immunity.…”
Section: Discussionmentioning
confidence: 98%
“…The CSF ADA level can exceed 10 units/L in bacterial or cryptococcal meningitis 18–21. The CSF ADA level can be elevated even in non-infectious diseases, such as immune-related adverse events provoked by immune checkpoint inhibitors, central nervous system lymphoma or leptomeningeal gliomatosis 22–24. Therefore, elevated CSF ADA levels alone cannot differentiate tuberculous meningitis from autoimmune GFAP astrocytopathy or other diseases.…”
Section: Discussionmentioning
confidence: 99%